Production of cellulase by immobilized whole cells of Haloarcula. - (:unkn) unknown (My University, 2012)
Halophilic Archaea are adapted to a life in the extreme conditions and some of them are capable of growth on cellulosic waste as carbon and energy source by producing cellulase enzyme. The production of cellulase using free and immobilized cells of halophilic archaeal strain Haloarcula 2TK2 isolated from Tuzkoy Salt Mine and capable of producing cellulose was studied. The cells were cultured in a liquid medium containing 2.5 M NaCl to obtain the maximum cellulase activity and immobilized on agarose or polyacrylamide or alginate. Optimal salt dependence of free and immobilized cells of Haloarcula 2TK2 was established and the effects of pH and temperature were investigated. Immobilization to Na-alginate enhanced the enzymatic activity of the haloarchaeal cells when compared to free cells and other polymeric supports. From the results obtained it is reasonable to infer that decomposition of plant polymers into simpler end products does occur at high salinities and cellulase producing haloarchael cells may be potentially utilized for the treatment of hypersaline waste water to remove cellulose.